SHyFTA, a Stochastic Hybrid Fault Tree Automaton for the modelling and simulation of dynamic reliability problems. (1st April 2016) - Chiacchio, Ferdinando; D'Urso, Diego; Compagno, Lucio; Pennisi, Marzio; Pappalardo, Francesco; Manno, Gabriele
Highlights: Discussion about the state of the art of expert systems and reliability assessment. Formalisation of the Stochastic Hybrid Fault Tree Automaton modelling technique. Conception of Hybrid Basic Events. Experimental Comparison of DFT and SHyFTA model for an industrial case study. Implementation of the SHyFTA in Simulink using MatCarloRE library. Abstract: Reliability assessment of industrial processes is traditionally performed with RAMS techniques. Such techniques are static in nature because they are unable to consider the multi-state operational and failure nature of systems and the dynamic variations of the environment in which they operate. Stochastic Hybrid Automaton appears to overcome this weakness coupling a deterministic and a stochastic process and integrating the features of a dynamic system with the concepts of dynamic reliability. At the state of the art, no attempts to enhance a formal RAMS technique with dynamic reliability has been tried, nor a computer-aided tool that plays as expert system has been coded yet. The aim of this paper is to fill this gap with a simulation formalism and a modelling tool able to combine the Dynamic Fault Tree technique and the Stochastic Hybrid Automaton within the Simulink environment. To this aim the MatCarloRE toolbox was adapted to interact with a Simulink dynamic system. The resulting assembly represents an important step ahead for the delivering of a user-friendly computer-aided tool for the dynamic reliability.